Characterization of a next‐generation piezo bimorph X‐ray mirror for synchrotron beamlines. (1st January 2015) - Alcock, Simon G.; Nistea, Ioana; Sutter, John P.; Sawhney, Kawal; Fermé, Jean‐Jacques; Thellièr, Christophe; Peverini, Luca
<x xml:space="preserve">Abstract</x> Piezo bimorph mirrors are versatile active optics used on many synchrotron beamlines. However, many bimorphs suffer from the `junction effect': a periodic deformation of the optical surface which causes major aberrations to the reflected X‐ray beam. This effect is linked to the construction of such mirrors, where piezo ceramics are glued directly below the thin optical substrate. In order to address this problem, a next‐generation bimorph with piezos bonded to the side faces of a monolithic substrate was developed at Thales‐SESO and optimized at Diamond Light Source. Using metrology feedback from the Diamond‐NOM, the optical slope error was reduced to ∼0.5 µrad r.m.s. for a range of ellipses. To maximize usability, a novel holder was built to accommodate the substrate in any orientation. When replacing a first‐generation bimorph on a synchrotron beamline, the new mirror significantly improved the size and shape of the reflected X‐ray beam. Most importantly, there was no evidence of the junction effect even after eight months of continuous beamline usage. It is hoped that this new design will reinvigorate the use of active bimorph optics at synchrotron and free‐electron laser facilities to manipulate and correct X‐ray wavefronts.